Objectives and importance of on-site research - Anane, Ivan (Technium Social Sciences Journal, 2024)
On-site investigation is a procedural and forensic tactical activity whose object is to directly perceive the place where a criminal act was committed, search, discover, reveale, fix, seize and examine evidence, including specifying their position and condition. On-site research is an immediate and irreplaceable activity, it must be carried out without delay and as completely as possible, since its repetition, although possible and recommended in certain situations, may lead to some results, but not always satisfactory. The importance of the investigation on the spot lies in the fact that the criminal investigation body directly perceives the circumstances in which the perpetrator acted, the objects he used in the implementation of the criminal resolution, the objects he touched in the criminal field, the ways of access and leaving the place where the act was committed. On-site investigation is an integrated activity in the criminal investigation. Since it is not the place where some considerations relating to the management and management of the investigation can be analysed, it must, however, be stressed that professional investigation work on the spot can fundamentally contribute to clarifying problems which, taken as a whole, the investigation of one or other of the offences must resolve.